Smoking Cessation in Individuals With Serious Mental Illness: A Randomized Controlled Trial of Two Psychosocial Interventions - Bennett, Melanie E. (J Dual Diagn, 2015)
OBJECTIVE: Smoking among individuals with serious mental illness is a critical public health problem. Although guidelines recommend bupropion for these smokers, many do not want to use medications for smoking cessation, express ambivalence about identifying a “quit date,” and do not have access to behavioral smoking cessation services integrated with mental health care. METHODS: Individuals with serious mental illness who smoked 10 or more cigarettes per day (N = 178) were randomized to either a multifaceted behavioral group intervention or a supportive group intervention, both of which were integrated within outpatient mental health services at three VA medical centers. Participants attended twice-weekly meetings for 12 weeks, provided information on their smoking at each meeting, and completed baseline and post-treatment assessments conducted by an assessor who was blind to condition. Primary outcomes collected at post-treatment included 1-week abstinence, number of cigarettes smoked per day during the last week, and number of quit attempts during the treatment period. Outcomes examined for a subset of participants who attended at least one intervention meeting (n = 152) included smoking abstinence for 1-, 2-, and 4-week blocks during the treatment period. Analyses conducted on those participants who attended three or more intervention meetings (n = 127) included time to 50% reduction in the number of cigarettes smoked and time to first quit attempt. RESULTS: Sixteen participants achieved abstinence (11.8%), smoking quantity was significantly reduced (baseline M = 15.2, SD = 9.8 to post-treatment M = 7.5, SD = 7.7, p < .0001), and most reported making a quit attempt (n = 88, 72.7%). There were no differences by study condition on any abstinence or reduction outcomes. Significant reductions in number of cigarettes smoked generally took place within the first two weeks; however, these reductions did not often translate into abstinence. CONCLUSIONS: Many participants reduced their smoking and sampled quitting during the study. Implementing smoking cessation services in mental health treatment settings is feasible and, if delivered in line with best practices, either a behavioral or a supportive approach can be helpful. Future research should examine ways to facilitate the transition from reduction to abstinence. This study was part of a clinical trial registered as NCT#00960375 at www.clinicaltrials.gov